О некоторых наименованиях металлов в Древневосточных и кавказских языках - Меликишвили, Г. A.
Melikišvili, G. А.; Names of Metals in Ancient Oriental and Caucasian Languages; engl. Résumé; zu pers. pūlād — urart. puluadi; hethit. kunna — georg. (r)qina; ḫurr. ušḫu — georg. ve(r)çḫ-li.